THE ROLE OF AUTHENTIC MATERIALS IN TEACHING A FOREIGN LANGUAGE - Sayitova Komila Hasanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article states the importance of using authentic materials in teaching a foreign language. In addition, the author notes that using authentic materials makes students get interested and motivated to learn a foreign language.